Synthesis of MgO nanostructure thin films via electrodeposition method for gas sensing applications - Lal, Nathu; Kumar, Amit; Kanhaiya Chawla; Sharma, Sandeep; Lal, Chhagan (Bangladesh Journal of Scientific and Industrial Research, 2023)
Magnesium oxide has long been intriguing due to several significant phenomena, including wide laser emission, spin electron reflectivity, and defect-induced magnetism. MgO nanostructures have a variety of applications, from spintronics to wastewater treatment, depending on their size and shape. Mg is sensitive material for hydrogen and forms MgH2, so we used Mg/MgO as a sensor to sense hydrogen gas in the present work. Magnesium oxide thin films were synthesized by electrodeposition technique using magnesium nitrate salt. XRD results suggested that the deposited thin films have a face-centered cubic structure. X-ray photoelectron spectroscopy was used to detect the elemental composition and chemical state with the general electronic structure of the sample. The morphology and growth of deposited nanostructure with elemental mapping of the thin film were investigated by SEM-EDS. The UV-visible analysis shows the calculated band gap for MgO thin filmwas 4.16 eV which is in the ultraviolet region. The I-V characteristics have been studied to find out the effect of hydrogenation on the synthesized MgO nanostructure and the sensitivity responseof about 31%. It is quiteevident that MgO nanostructure may be used for gas sensing applications (such as H2 gas). Bangladesh J. Sci. Ind. Res. 58(2), 119-128, 2023